Calcium Fructoborate Prevents Skin Cancer Development in Balb-c Mice - Kisacam, Mehmet Ali; Kocamuftuoglu, Gonca Ozan; Ozan, Ibrahim Enver; Yaman, Mehmet; Ozan, Sema Temizer (Springernature, 2020)
Tumor microenvironment, genetic, and non-genetic factors are responsible for the atypical metabolic feature of cancer cells. Aberrant activity of PI3K/Akt pathway, increased glycolytic flux, and decreased intracellular pH gradient are the leading causes of this feature. Calcium Fructoborate (CaFB), a sugar-borate ester, has major benefits for human health. The aim of this study was to explore the implication of CaFB on experimentally induced skin cancer in vivo. According to the treatment, 92 female Balb-c mice are divided into six groups: control, CaFB (3 mg/kg/day), 7,12-Dimethylbenz(a)anthracene (DMBA)+12-O-tetradecanoylphorbol-13-acetate (TPA) (97.5 nmol DMBA, 6.5 nmol TPA), T1: CaFB+DMBA+TPA (3 mg/kg/day CaFB together with DMBA), T2: DMBA+CaFB+TPA (3 mg/kg/day CaFB together with TPA), T3: DMBA+TPA+CaFB (3 mg/kg/day CaFB after tumor formation). Topical DMBA and TPA application resulted in a significant increase in the protein levels, immunoreactivity, and mRNA expression of HRAS, HIF1 alpha, Akt, and PTEN (p< 0.05). Moreover, an increase in the number of TUNEL-positive cells was observed in DMBA-TPA group compared with the control group (p< 0.05). CaFB application reduced the protein levels, immunoreactivity, and mRNA expressions of HRAS, HIF1 alpha, Akt, and PTEN and also decreased the number of TUNEL-positive cells. Recent evidence obtained from our study validated that CaFB treatment may have skin cancer-preventing effect.
Keywords: Skin cancer; HRAS; Akt; Calcium Fructoborate; Skin cancer-preventing effect